Observation, assessment and planning in inclusive autism education supporting learning and developing - Conn, Carmel (London Routledge, 2016)
This practical resource takes a holistic view of the learning and development of children with autism, taking into account the nature of their social-emotional learning and the transactional nature of difficulty. Using an interdisciplinary approach, this accessible and practical text invites practitioners, pupils and parents to reflect on their understandings, beliefs and values and to make appropriate adjustments in their practice. Split into five chapters, this book covers some of the main issues involved in observation-based teaching and learning.
Figures and tables -- Preface 1. Taking an educational perspective on the autistic pupil -- 2. Making observations -- 3. Listening to children -- 4. Assessment and planning -- 5. Compiling pupil profiles and evaluating practice -- References -- Index
Includes bibliographical references (pages 111-116) and index.
Keywords: Autistic children -- Education